Absorption cross section of building materials at mm wavelength in a reverberation chamber. (12th January 2017) - Micheli, D; Delfini, A; Pastore, R; Marchetti, M; Diana, R; Gradoni, G
Abstract: The reverberation chamber (RC) method is used to estimate the average absorption cross section of building materials at mm wave frequencies. Analysed samples include concrete, travertine and bricks of different types. The investigation is carried out in the frequency range between 50 GHz and 68 GHz, which is of interest in the next generation of mobile telecommunication system. A cylindrical cavity is transformed into a RC through the use of a mechanical model stirrer. The chamber field is statistically homogeneous and depolarized; therefore it can be used to probe the average response of the sample under test. In particular, through a differential measure of the average quality factor (average insertion loss) it is possible estimate the fraction of power absorbed by the sample under test. Several cube-shape samples have been characterized and compared. Obtained results show that analysed samples have remarkably different levels of the electromagnetic wave absorption, depending on both material density and chemical composition. The absorption of pure water is used as a baseline to determine the dynamic range of the measurement.